Genomic alterations in the YAP/TAZ pathway are associated with stem cell-like castration-resistant prostate cancer - Roskes, Marjorie L; Martinez-Fundichely, Alexander; Cohen, Sandra; Balaban, Metin; Wong, Chen Khuan; Li, Weiling; Gonzalez, Tonatiuh A; Tehim, Anisha B; Xu, Hao; ElNaggar, Shahd; Myers, Matthew; Bareja, Rohan; et al. (medRxiv : the preprint server for health sciences, 2025)
Castration-resistant prostate cancer (CRPC) is an aggressive disease exhibiting multiple epigenomic subtypes: androgen receptor-dependent CRPC-AR, and lineage plastic subtypes CRPC-SCL (stem cell-like), CRPC-WNT (Wnt-dependent), and CRPC-NE (neuroendocrine). By transcriptomic profiling of tissue, and whole-genome sequencing (WGS) of tissue and cell-free DNA (cfDNA) from 500 samples, we relate genomic variants with epigenomic state. We find lineage plasticity is associated with higher epigenomic and genomic heterogeneity. Samples with CRPC-SCL show higher chromosomal instability. We find DNA alterations, particularly chromosomal rearrangements, in the YAP/TAZ pathway associated with CRPC-SCL. For example, complex rearrangements on chromosome 4, which are supported by patient-matched 3D genome architecture data, decrease promoter interactions of , a YAP/TAZ pathway inhibitor, with its enhancers. Together, the genomic variants in the pathway can predict CRPC-SCL with 79% accuracy. We show the utility of cfDNA WGS for joint inference of epigenomic state and genomic variants, which can guide patient stratification for clinical decisions. This study reveals genomic variants associated with the presence of lineage-plastic CRPC stem cell-like state. We leverage the utility of minimally invasive cfDNA sequencing to obtain genomic and epigenomic insights about CRPC heterogeneity, which have implications for patient stratification for treatment decisions.